Decolonial AestheSis at the 11th Havana Biennial - Ferrera Balanquet, Raul Moarquech; Rojas-Sotelo, Miguel (Social Text Online, 2013)
The written curatorial statement from the organizing committee of the 11th Havana Biennial arrived via email the same day that we were preparing a dossier for the Romanian magazine IDEA. As we put together a brief history of “Decolonial Aesthetics” meetings and some portions of the “Decolonial Manifesto,” we discussed the need to bring to the biennial some of the critical and creative processes emanating from the decolonial collective. Previous editions of the biennial were overcharged with doses of “postmodernity,” marginal notes on the “postcolonial” condition, and celebrations of the “altermodern” (with its postproduction and relational dimensions). These were present in the curatorial practices, as well as in several of the presentations at the Theoretical Forum during the 2006 and 2009 editions. As we kept reading through the Biennial‘s curatorial statement, its content promoted a heated discussion among us where the idea of presenting a panel on decolonial aestheSis at the Havana Biennial became seen as not only relevant, but also, and above all, necessary.
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Sud (corpus analysé); 5-Auteur.rice PANDC; _Nettoyé